Personalized Drug Sensitivity Screening for Bladder Cancer Using Conditionally Reprogrammed Patient-derived Cells - Kimmo Kettunen; Peter J. Boström; Tarja Lamminen; Taija Heinosalo; Gun West; Irena Saarinen; Katja Kaipio; Juha Rantala; Chris Albanese; Matti Poutanen; Pekka Taimen (Elsevier B.V., 2022)
Many patients with muscle-invasive bladder cancer (BC) are either ineligible for or do not benefit from cisplatin-based chemotherapy, and there is an unmet need to estimate individuals’ drug sensitivities. We investigated the suitability of conditionally reprogrammed (CR) cells for the characterization of BC properties and their feasibility for personalized drug sensitivity screening. The CR cultures were established from six BC tumors with varying histology and stage. Four cultures were successfully propagated for genomic, transcriptomic, and protein expression profiling and compared to the parental tumors. Two out of four CR cultures (urothelial carcinoma and small cell neuroendocrine carcinoma [SmCC]) corresponded well to their parental tumors and underwent drug sensitivity screening to identify novel drugs for the respective tumors. Both cultures were sensitive to standard BC chemotherapy agents (eg cisplatin and gemcitabine) and to conventional drugs such as taxanes and inhibitors of topoisomerase and proteasome. The SmCC cells were also sensitive to <a href="https://www.sciencedirect.com/topics/medicine-and-dentistry/hydroxymethylglutaryl-coenzyme-a-reductase-inhibitor" title="Learn more about Hydroxymethylglutaryl Coenzyme A Reductase Inhibitor from ScienceDirect's AI-generated Topic Pages">statins (eg, atorvastatin and pitavastatin). In summary, after confirming their representativeness and origin, we conclude that CR cells are a feasible platform for personalized drug sensitivity testing and might thus add to the approaches used to personalize BC treatment strategies.
Patient summary
We investigated the conditional reprogramming method for generating patient-derived bladder cancer cell cultures and studied their feasibility for planning personalized treatment strategies.